The Effect of Intracanal Medicaments on Microleakage of Mineral Trioxide Aggregate Apical Plugs - Nabavizadeh, Mohammadreza; Moazzami, Fariborz; Bahmani, Mohsen; Mirhadi, Hossein (Iranian Endodontic Journal, 2017)
Introduction: The purpose of this in vitro study was to evaluate the effect of calcium hydroxide, double and triple antibiotic paste on the sealing ability of mineral trioxide aggregate (MTA) apical plugs. Methods and Materials: A total of 90 extracted teeth with single canals were prepared and randomly divided into four experimental groups (n=20). Intra-canal medicaments were applied for 3 weeks. MTA was placed through the access opening and condensed to the apical area and then fluid filtration technique was utilized to evaluate sealing ability after 1, 7, 14 and 30 days. Results: Triple antibiotic paste significantly reduced the sealing ability of MTA plug compared with double antibiotic paste (P=0.024) and normal saline (P=0.04) groups on day 1. The sealing ability was not different on days 14 and 30 between experimental groups (P>0.05). Conclusion: All medicaments can be used without any long term effect on microleakage. Keywords: Calcium Hydroxide; Double Antibiotic Paste; Endodontic Regeneration; Microleakage; Triple Antibiotic Paste